Toward a More Efficient Taxation System in New Zealand - Mourougane, Annabelle (OECD Economics Department Working Papers, 2007)
After the radical reforms undertaken in the 1980s, the NZ tax system has long been regarded as one of most efficient within the OECD, and is based on a comprehensive income approach. Looking forward, the country will require a tax regime that helps the economy to continue raising living standards, supports savings and investment and copes with emerging pressures such as increasing geographic mobility of labour and capital. In this context, it will be important to have in place a clear long-term direction for the tax system to guide reforms. There are at least two broad options that are worth considering: adapting the system within a comprehensive income approach or adopting a dual income tax system. Future changes to the tax system need to be consistent with the approach ultimately adopted. In any case, a number of limitations of current tax bases will need to be tackled. This Working Paper relates to the 2007 OECD Economic Survey of New Zealand (www.oecd.org/eco/surveys/nz)